Teacher influence on the training of university research students - Camones Villacorta , Jhonny Erick (2025)
The training of student researchers constitutes a critical challenge for higher education, especially in contexts of uncertainty. This study analyzes the influence of university teaching on the formation of student research competencies at the Universidad Nacional Mayor de San Marcos (UNMSM), considering the dimensions of planning, conduction, and evaluation of the teaching-learning process. A correlational quantitative approach with a non-experimental cross-sectional design was used. The sample included 73 research professors selected probabilistically. Two validated questionnaires with Likert scale were applied. Results show significance levels p < 0.05 and Wald scores above 4 for all dimensions, confirming direct and significant influence of teaching on student research training. The existence of a positive causal relationship between teaching quality and the development of university research competencies is concluded.